2013
DOI: 10.1186/1755-8166-6-47
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of two de novo 4q35-qter deletions characterized by array-CGH

Abstract: BackgroundThe 4q- syndrome is a well known genetic condition caused by a partial terminal or interstitial deletion in the long arm of chromosome 4. The great variability in the extent of these deletions and the possible contribution of additional genetic rearrangements, such as unbalanced translocations, lead to a wide spectrum of clinical manifestations. The majority of reports of 4q- cases are associated with large deletions identified by conventional chromosome analysis; however, the widespread clinical use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Essential features of this syndrome include mild craniofacial and digital dysmorphism, developmental delay, growth retardation, skeletal and cardiac anomalies, and autism spectrum disorder [ 2 ]. A broad spectrum of clinical manifestations has been observed partly due to the variability in the extent of the deletions and the possible additional contribution of other genetic rearrangements, such as unbalanced translocations [ 3 ]. Many reports of 4q- cases associated with large deletions could be detected by conventional chromosome analysis; however, in recent years the reports of submicroscopic chromosomal aberrations associated with 4q- phenotype increased as a result of the widespread diagnostic use of array comparative genomic hybridization (a-CGH) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Essential features of this syndrome include mild craniofacial and digital dysmorphism, developmental delay, growth retardation, skeletal and cardiac anomalies, and autism spectrum disorder [ 2 ]. A broad spectrum of clinical manifestations has been observed partly due to the variability in the extent of the deletions and the possible additional contribution of other genetic rearrangements, such as unbalanced translocations [ 3 ]. Many reports of 4q- cases associated with large deletions could be detected by conventional chromosome analysis; however, in recent years the reports of submicroscopic chromosomal aberrations associated with 4q- phenotype increased as a result of the widespread diagnostic use of array comparative genomic hybridization (a-CGH) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, molecular karyotyping has only previously been applied twice in prenatal cases with chromosome 4 long arm distal deletions that encompassed the 4q35 region. Manolakos et al [] reported two prenatally detected male fetuses with de novo teminal deletions on the long arm of one of the chromosome 4s. In both cases, the karyotypes were described as 46,XY,del(4)(q35.1).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome 4 long arm deletion is a rare chromosomal deletion syndrome with a wide range of phenotypic findings, and the severity of the malformations depends on both the size of the deletion and the location of the breakpoint [Xu et al, ]. Common phenotypic characteristics of large chromosome 4 long arm deletions are mild dysmorphic features, craniofacial, digital, skeletal, gastrointestinal, cardiac, and urogenital anomalies, as well as developmental delay [Manolakos et al, ]. Small deletions in the distal portion of chromosome 4's long arm do not seem to result in gross congenital malformations.…”
Section: Introductionmentioning
confidence: 99%
“…according to standard procedures. CMA was carried out using oligonucleotide aCGH platforms (Agilent technologies, Santa Clara, CA) using an 80 Kb resolution array (kit 60k) as described elsewhere [6]. The reference DNA was of male gender.…”
Section: Methodsmentioning
confidence: 99%